Influence of a blend of functional oils or monensin on nutrient intake and digestibility, ruminal fermentation and milk production of dairy cows - Ferreira de Jesus, E. [UNESP]; Del Valle, T. A.; Calomeni, G. D.; Silva, T. H.; Takiya, C. S.; Vendramini, T. H.A.; Paiva, P. G.; Silva, G. G.; Netto, A. S.; Rennó, F. P. (Elsevier, 2016)
Cashew nut shell liquid (CNSL) and castor oil (CO) are considered functional oils since they present antitumor, antioxidant, gastroprotective, and antibiotic properties. The objective of this study was to evaluate the effects a commercial blend of functional oils (CNSL and CO) and monensin supplementation on nutrient intake and total tract apparent digestibility, ruminal fermentation, milk yield and composition, N utilization, microbial protein synthesis, and blood metabolites of dairy cows. Twenty-four multiparous Holstein cows (150.2 ± 61.4 days in milk, 619 ± 76 kg of BW and 29.1 ± 4.0 kg/d of milk yield, mean ± SD) were used in a replicated 3 × 3 Latin square experimental design, in which six ruminally cannulated cows were used to assess ruminal fermentation. The animals were randomly assigned to one of the following three treatments: control (CON; without additive); 500 mg/kg DM of functional oil (FO; commercial blend of CNSL and CO), and 22 mg/kg DM of monensin sodium (MON). The treatments did not affect either nutrient intake or digestibility of diets. Both feed additives provided an increase in ruminal propionate molar proportion compared to CON. In addition, FO increased ruminal propionate concentration when compared to MON and CON. Although both additives increased (P < 0.01) milk and protein yields, MON had lower milk fat concentration compared to CON, not differing from FO. Monensin and FO increased milk nitrogen excretion. Neither rumen microbial N synthesis nor blood glucose concentration were changed by the supplements. Finally, FO decreased (P < 0.001) blood urea concentration compared to CON or MON, besides increasing milk yield without altering nutrient intake; thus, it might be an alternative to monensin in lactating cow diets.
Keywords: Additives; Antimicrobial; Cashew nut shell liquid; Castor oil; Ionophore; Phenolic lipids